Au-delà des conflits de mémoire : transitions numériques vers une écriture participative du patrimoine culturel de l’Indiaocéanie - Nathalie Noël; Jean-François Rebeyrotte; Camila Arêas (Humanités Numériques)
The databases of the inventory of cultural heritage in France, which are often formatted according to the logic of scientific expertise of tangible heritage, do little to integrate the discourse logics of the “popular” expertise generated by intangible heritage. However, the open science movement, notably through open source software, open data and citizen science, opens up perspectives for the participatory writing of cultural heritage. With the example of the database of the Regional Inventory Service of Reunion Island, we will see how the logic of open science leads interdisciplinary communities to question the knowledge modelling of the cultural heritage of a post-colonial French society, in order to overcome the conflicts involved in writing the memory of an Indiaoceanic territory.